2012
DOI: 10.2319/052212-419.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 980-nm diode laser–aided circumferential supracrestal fiberotomy on fluorosed root surfaces

Abstract: Objective: To evaluate and compare the root surface morphological changes after 980-nm diode laser-aided circumferential supracrestal fiberotomy (CSF) on fluorosed and non-fluorosed teeth. Materials and Methods: The sample comprised 27 orthodontic patients (14 males and 13 females; mean age 5 17.3 years) with and without fluorosis, from whom 40 fluorosed and 40 nonfluorosed premolar teeth were extracted for orthodontic reasons. Conventional (control group) and laser-aided (experimental group) CSF was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
(15 reference statements)
1
11
0
1
Order By: Relevance
“…The present findings are consistent with previous reports of a significant reduction in the relapse of orthodontically rotated teeth following CSF performed as an adjunct to mechanical retention ( Dhingra et al, 2013 , Littlewood et al, 2006 , Young et al, 2013 , Pinson and Strahan, 1974 , Taner et al, 2000 ). Interestingly, by 12 months after retention, we found a mean relapse rate of 10.8% for teeth subjected to fiberotomy; this was similar to the rate in a controlled study reported by Crum and Andreasen ( Crum and Andreasen, 1974 ), indicating the potentially stabilizing effect of fiberotomy on orthodontically rotated teeth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings are consistent with previous reports of a significant reduction in the relapse of orthodontically rotated teeth following CSF performed as an adjunct to mechanical retention ( Dhingra et al, 2013 , Littlewood et al, 2006 , Young et al, 2013 , Pinson and Strahan, 1974 , Taner et al, 2000 ). Interestingly, by 12 months after retention, we found a mean relapse rate of 10.8% for teeth subjected to fiberotomy; this was similar to the rate in a controlled study reported by Crum and Andreasen ( Crum and Andreasen, 1974 ), indicating the potentially stabilizing effect of fiberotomy on orthodontically rotated teeth.…”
Section: Discussionsupporting
confidence: 93%
“…These findings led us to speculate that circumferential supracrestal fiberotomy (CSF) would release the tension on the supra-alveolar fibers following tooth rotation, thereby reducing the risk of rotational relapse ( Lv et al, 2009 ). Further studies have validated the effect of CSF on reducing this type of relapse ( Block et al, 1998 , Dhingra et al, 2013 , Littlewood et al, 2006 ). However, it is important to note the amount and location of relapse for proper clinical evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…[18] and showed that there were differences in surface morphology among fluorosed and nonfluorosed roots in the control group. The root specimens of both fluorosed and nonfluorosed teeth irradiated by diode laser exhibited no evidence of smear layer, laser-induced pitting or cavitation, linear cuts/ markings, carbonization of surface, and heat-induced surface cracking.…”
Section: Effect Of 980-nm Diode Laser-aided Circumferential Supracresmentioning
confidence: 95%
“…[16] Effect of desensitizing agents on fluorosed and nonfluorosed teeth-in vitro Scanning electron microscope analysis • SEM study to evaluate the effect of densitizing agents on dentinal tubular morphology in fluorosed teeth. [17] Effect of 980-nm diode laser-aided circumferential supracrestal fiberotomy (CSF) on fluorosed root surfaces [18] Ongoing Projects • Effect of topical application of guduchi gel (herbal extract) in the treatment of periodontitis in fluorosed and nonfluorosed patients. Clinical studies to evaluate the peridontal changes caused by fluorosis [2] Though the effect of fluoride on reduction of dental caries is well-established, its effect on periodontal tissues is obscure.…”
Section: Study To Evaluate the Periodontal Changes Caused By Fluorosismentioning
confidence: 99%
“…En la actualidad, han sido propuestos nuevos métodos para llevar a cabo la FCS, entre los cuales están la terapia láser de bajo nivel, la electrocirugía y la asistida con láser, mas los resultados aún no son del todo claros ( [16][17][18][19][20][21][22][23][24][25] ). Por tanto, el objetivo de la presente revisión es conocer una visión actual de la técnica de FSC, la evolución de esta técnica y las nuevas tendencias para realizarla a través de una evaluación contemporánea de la literatura científica.…”
Section: Introductionunclassified